Sex Disaggregated Trajectories of Status Offenders: Does CINS/FINS Status Prevent Male and Female Youth From Becoming Labeled Delinquent? - Jennings, Wesley G. (American journal of criminal justice, 2011)
This study sought to provide a more recent and longitudinal examination of the effect of formal processing on status offenders’ subsequent delinquency using data from a large sample of first-time referral status offenders in the state of Florida. Results from semi-parametric group-based trajectory models suggested that roughly half of the status offenders subsequently accumulated delinquent arrests in adolescence following their initial referral for a status offense. Furthermore, the number and type of trajectory groups were more similar than different across sex. Study limitations and policy implications are also discussed.